Oxygen reduction on nanocrystalline ruthenia – local structure effects. Issue 2 (3rd December 2014) - Abbott, Daniel F.; Mukerjee, Sanjeev; Petrykin, Valery; Bastl, Zdeněk; Halck, Niels Bendtsen; Rossmeisl, Jan; Krtil, Petr
Abstract : Nanocrystalline ruthenium dioxide and doped ruthenia of the composition Ru1− x M x O2 (M = Co, Ni, Zn) with 0 ≤ x ≤ 0.2 were prepared by the spray-freezing freeze-drying technique. Abstract : Nanocrystalline ruthenium dioxide and doped ruthenia of the composition Ru1− x M x O2 (M = Co, Ni, Zn) with 0 ≤ x ≤ 0.2 were prepared by the spray-freezing freeze-drying technique. The oxygen reduction activity and selectivity of the prepared materials were evaluated in alkaline media using the RRDE methodology. All ruthenium based oxides show a strong preference for a 2-electron oxygen reduction pathway at low overpotentials. The catalysts' selectivity shifts towards the 4-electron reduction pathway at high overpotentials ( i.e. at potentials below 0.4 V vs. RHE). This trend is particularly noticeable on non-doped and Zn-doped catalysts; the materials containing Ni and Co produce a significant fraction of hydrogen peroxide even at high overpotentials. The suppression of the 4-electron reduction pathway on Ni and Co-doped catalysts can be accounted for by the presence of the Ni and Co cations in the cus binding sites as shown by the DFT-based analyses on non-doped and doped catalysts.